HOUSING PUBLIC POLICIES AND THE LIMITS OF THE JUDICIARY’S PERFORMANCE IN THE GUARANTEE OF THIS SOCIAL RIGHT (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This work highlights the importance of the right to housing on the international sphere and, mainly, as a fundamental social right inserted on the Brazilian 1988 Constitution. A brief analyzes about the country’s urbanization historical process is made, also mentioning the significant housing deficit that still exists. On this context, the function of each one of the government’s branches on the achievement of the State’s goals is addressed, mainly in relation to the elaboration and execution of public policies, highlighting the judges’ paper in ensuring the citizens’ rights from the contemporary constitutional right, who should also observe the constitutional limits imposed to the judicial intervention on the public policies. Specially about the housing public policies, decisions of the Brazilian Judiciary in favor of this fundamental right are brought.